Analisis Faktor-Faktor yang Memengaruhi Penerimaan Teknologi Menggunakan Kuesioner Technology Acceptance Model (TAM) pada E-Learning Google Classroom di SMK Negeri 2 Kupang - Herald Anwar Bhasarie; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In this age, the use of technology is increasing, including internet usage. Internet make a lot of changes in many aspect of life, one of which is education. During the current pandemic, where teaching and learning process have to use e-learning. In general, e-learning that often use is Google Classroom. Location of this research are in SMK Negeri 2 Kupang. The purpose of this research is to find out he factors that support on the acceptance of technology at SMK Negeri 2 Kupang. The concept of this research are to analysis factor using technology acceptance model (TAM) questionnaire, which consists of 7 factors: complexity, self-efficacy, time limiting, usability, ease of use, intention and ease of use technology. Methodology that was used in this study, are by formulate hypotheses and path analysts to analyze the connection between factors. Based on the results of hypotheses and path analysts, can be concluded that factor of complexity, time constraints, ease of use, and intention affect ease of use, and self-efficacy has no effect on ease of use.